Інклюзивна освіта як чинник формування соціальних компетентностей дітей з інвалідністю в сучасній системі освіти України - Бучко, Христина Ігорівна; Buchko, Khrystyna Ihorivna (Національний університет "Львівська політехніка", 2025)
У поданій роботі досліджується інклюзивна освіта як чинник формування соціальних компетентностей дітей з інвалідністю в сучасній системі освіти України. Інклюзія розглядається не лише як механізм забезпечення рівного доступу до знань, а й як інструмент соціалізації та інтеграції у суспільство. Проаналізовано нормативно-правову базу України та міжнародні документи, що закріплюють право на інклюзивну освіту, зокрема Конвенцію ООН про права осіб з інвалідністю. Визначено ключові умови ефективного впровадження інклюзії: підготовка педагогів, створення адаптованого освітнього середовища, міжсекторальна співпраця та державна політика. Показано, що інклюзивна освіта сприяє розвитку соціальних компетентностей — толерантності, емпатії, комунікативних навичок — та формуванню демократичного, інклюзивного суспільства. Актуальність теми зумовлена необхідністю забезпечення рівних прав і можливостей для дітей з інвалідністю та подолання бар’єрів у доступі до якісної освіти. Мета дослідження полягає у виявленні особливостей формування соціальних компетентностей дітей з інвалідністю в умовах інклюзивної освіти. Відповідно до мети дослідження визначено наступні завдання: - Визначити базові принципи розвитку сучасних тенденцій інклюзивної освіти; - Проаналізувати нормативно-правове поле інклюзивної освіти дітей з інвалідністю на міжнародному та національному рівнях. - З’ясувати особливості набуття і розвитку соціальних навичок у дітей з інвалідністю. - Розглянути роль соціальної інклюзії в освіті щодо ліквідації інституційних бар’єрів та окреслити особливості розвитку соціальних компетентностей дітей з інвалідністю; - Розробити та провести емпіричне дослідження стосовно вивчення особливостей розвитку соціальних компетентностей дітей з інвалідністю в системі інклюзивної освіти (на прикладі Закладу загальної середньої освіти № 87 Львівської міської ради ім. Ірини Калинець. Об’єкт дослідження: інклюзивна освіта в сучасній системі освіти України. Предмет дослідження: характерні особливості розвитку соціальних компетентностей дітей з інвалідністю в системі інклюзивної освіти України. У першому розділі магістерської кваліфікаційної роботи «Засадничі положення розвитку сучасних тенденцій інклюзивної освіти» проведено аналіз наукової літератури та міжнародних і національних нормативно-правових документів. У другому розділі роботи «Особливості впровадження інклюзивних практик як чинників формування соціальних компетентностей дітей з інвалідністю в сучасній системі освіти України» виконано аналіз процесу формування соціальних компетентностей у дітей з інвалідністю в умовах впровадження інклюзивних освітніх практик у сучасній українській системі освіти. У третьому розділі магістерської роботи «Дослідження формування соціальних компетентностей дітей з інвалідністю в умовах інклюзивної освіти в Україні» на прикладі Закладу загальної середньої освіти № 87 Львівської міської ради імені Ірини Калинець виявлено специфіку, умови та педагогічні підходи до формування соціальних компетентностей дітей з інвалідністю в інклюзивному освітньому середовищі сучасної української школи.

This MSW paper examines inclusive education as a factor in the development of social competencies in children with disabilities within the modern education system of Ukraine. Inclusion is considered not only as a mechanism for ensuring equal access to knowledge but also as a tool for socialization and integration into society. The regulatory and legal framework of Ukraine, as well as international documents that enshrine the right to inclusive education, particularly the UN Convention on the Rights of Persons with Disabilities, are analyzed. Key conditions for the effective implementation of inclusion are identified: teacher training, the creation of an adapted educational environment, cross-sectoral cooperation, and public policy. It is shown that inclusive education contributes to the development of social competencies—tolerance, empathy, communication skills—and the formation of a democratic, inclusive society. The relevance of the topic is determined by the need to ensure equal rights and opportunities for children with disabilities and to overcome barriers to access to quality education. The purpose of the study is to identify the characteristics of the formation of social competencies of children with disabilities in the context of inclusive education. In accordance with the purpose of the study, the following tasks have been identified: - To identify the basic principles of the development of modern trends in inclusive education; - To analyze the regulatory and legal framework for inclusive education of children with disabilities at the international and national levels. - To identify the peculiarities of the acquisition and development of social skills in children with disabilities. - To consider the role of social inclusion in education in eliminating institutional barriers and to outline the peculiarities of the development of social competencies in children with disabilities; - Develop and conduct empirical research on the peculiarities of the development of social competencies of children with disabilities in the inclusive education system (using the example of the Iryna Kalynets Secondary School No. 87 of the Lviv City Council). Object of research: inclusive education in the modern education system of Ukraine. Subject of the study: characteristic features of the development of social competencies of children with disabilities in the inclusive education system of Ukraine. The first chapter of the master's thesis “Fundamental Provisions for the Development of Modern Trends in Inclusive Education” analyzes scientific literature and international and national regulatory and legal documents. The second chapter of the thesis, “Features of the implementation of inclusive practices as factors in the formation of social competencies of children with disabilities in the modern education system of Ukraine,” analyzes the process of forming social competencies in children with disabilities in the context of the implementation of inclusive educational practices in the modern Ukrainian education system. The third chapter of the master's thesis, “Research on the formation of social competencies of children with disabilities in the context of inclusive education in Ukraine,” using the example of the Iryna Kalynets Secondary School No. 87 of the Lviv City Council, reveals the specifics, conditions, and pedagogical approaches to the formation of social competencies in children with disabilities in the inclusive educational environment of modern Ukrainian schools.
Inclusive Education as a factor in developing social competencies of children with disabilities in Ukraine's modern education system
Keywords: 8.231.00.01; інклюзивна освіта; діти з інвалідністю; соціальні навички; inclusive education; children with disabilities; social skills